PENGARUH MINAT BACA TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS II SD NEGERI 2 MERBAU MATARAM LAMPUNG SELATAN - Kharismaya, Melinda; Qomario, Qomario; Mashari, Ali (JURNAL ILMU PENDIDIKAN, 2023)
This study aims to determine the effect of reading interest on the learning outcomes of second-grade students at SD Negeri 2 Merbau Mataram, South Lampung. The research was conducted at SD Negeri 2 Merbau Mataram, South Lampung, Merbau Mataram District, South Lampung Regency for the academic year 2021/2022. This study uses a quantitative method with the type of pre-experimental one-group pretest-posttest design which is used to determine the effect of a treatment on research subjects. The samples in this study were all students of class II SD Negeri 2 Merbau Mataram South Lampung, totaling 33 students. The data of this study were obtained from the pretest and post-test scores, with 15 multiple-choice instruments as the instrument. The results of hypothesis testing obtained the value of tcount≥ttable, namely 2.6889 2.042. Then Ho is accepted which means there is an influence interest in reading on the learning outcomes of students in class II Merbau Mataram, South Lampung.